Detecting Residual Awareness in Patients With Prolonged Disorders of Consciousness: An fNIRS Study - Li, Meng; Yang, Yi; Zhang, Yujin; Gao, Yuhang; Jing, Rixing; Dang, Yuanyuan; Chen, Xueling; He, Jianghong; Si, Juanning (Frontiers in Neurology, 2021)
In the past few years, advances in neuroimaging technologies have provided in-sights into detecting residual consciousness and assessing cognitive abilities in pa-tients with disorders of consciousness (DOC). Functional near-infrared spectroscopy (fNIRS) is non-invasive, portable, and can be used for longitudinal bedside monitor-ing, making it uniquely suited for evaluating brain function in patients with DOC at appropriate spatio-temporal resolutions. In this pilot study, an active com-mand-driven motor imagery (MI) paradigm based on fNIRS was used to detect cov-ert consciousness in patients with prolonged DOC. A support vector machine (SVM) classifier was used to classify yes-or-no responses. The results showed that relatively reliable responses were detected from three out of five patients in a minimally con-sciousness state (MCS). One of the patients answered all the questions accurately when assessed according to this method. This study confirmed the feasibility of using portable fNIRS technology to detect covert cognitive ability in patients with pro-longed DOC by active command-driven motor imagery. We hope to detect the exact level of consciousness in DOC patients who may have a higher level of conscious-ness.